Analisis Dampak Strategi MSDM pada Kinerja Pemasaran: Peran Moderasi Budaya Organisasi - Helendra Helendra; Haderah Haderah; Andis Febrian; Zulvaruri Sintia Putri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The increasingly fierce competition in digital marketing requires MSMEs and startups to not only rely on promotional strategies, but also on human resources and a work culture that supports rapid adaptation. In practice, many digital businesses face limitations in human resource management and organisational culture that are not yet well-defined, resulting in unstable marketing performance. This research is important to explain the internal factors that can strengthen marketing success in digital-based MSMEs and startups. This study aims to analyse the influence of HRM strategies on marketing performance and to examine the moderating role of organisational culture in digital-based MSMEs and startups in Padang and Bukittinggi. This is an explanatory quantitative study with a cross-sectional survey design. The research population consists of digital-based MSMEs and startups in Padang and Bukittinggi that carry out marketing activities through digital channels. The sampling technique used purposive sampling with a sample size of 250 respondents, namely business owners or managers who understand HRM practices, work culture, and marketing activities. Data were collected using a five-point Likert scale questionnaire and analysed using PLS SEM through SmartPLS. The results of the study indicate that HRM strategies have a positive effect on marketing performance, organisational culture has a positive effect on marketing performance, and organisational culture has been proven to strengthen the effect of HRM strategies on marketing performance. The implications of this study confirm that improving the marketing performance of digital businesses needs to be supported by strategic human resource management and an adaptive, collaborative, and customer-oriented organisational culture.